2018
DOI: 10.1007/s13318-018-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the P-gp Inhibitor Tariquidar in Rats After Intravenous, Oral, and Intraperitoneal Administration

Abstract: Background and objectiveP-glycoprotein (P-gp), a transmembrane transporter expressed at the blood–brain barrier, restricts the distribution of diverse central nervous system-targeted drugs from blood into brain, reducing their therapeutic efficacy. The third-generation P-gp inhibitor tariquidar (XR9576) was shown to enhance brain distribution of P-gp substrate drugs in humans. Oral bioavailability of tariquidar was found to be low in humans requiring the compound to be administered intravenously, which hinders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The difference in the pharmacokinetics of oral administration between Tariquidar and α-MG was further compared. Data were collected from Matzneller et al [ 30 ] and Li et al [ 31 ]. Results showed that the absolute bioavailability (F) in the solution dosage form was 71.6% for Tariquidar at a dosage of 15 mg/kg and 90.2% for α-MG at a dosage of 20 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the pharmacokinetics of oral administration between Tariquidar and α-MG was further compared. Data were collected from Matzneller et al [ 30 ] and Li et al [ 31 ]. Results showed that the absolute bioavailability (F) in the solution dosage form was 71.6% for Tariquidar at a dosage of 15 mg/kg and 90.2% for α-MG at a dosage of 20 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the effect of the brain efflux transporters on the uptakes of [ 18 F]FPEB in the rat brain. TQD had been considered a highly selective inhibitor of P‐gp, but subsequent studies showed that TQD also inhibits Bcrp (Bankstahl et al, ; Fougère et al, ; Kuntner et al, ; Matzneller et al, ; Robey et al, ). Therefore, in the present study, a combination of pharmacological inhibition and genetic ablation approaches to the efflux transporter systems was used.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the effects of liver failure on the expression and function of ABC transporters at BBB are often dependent on species of ABC transporters, brain regions, duration of liver failure and types of liver failure. Moreover, P-GP and BCRP are also highly expressed in intestine and liver and mediate excretion of their substrate drugs via intestinal wall and bile duct, demonstrating important roles in pharmacokinetics and pharmacology/toxicity of drugs [ 86 , 87 ]. Several reports demonstrated that liver failure downregulated the function and expression of intestinal P-GP [ 88 ], but increased the expression of hepatic BCRP and P-GP [ 89 , 90 ].…”
Section: Future Perspectivesmentioning
confidence: 99%